2014
DOI: 10.4155/bio.13.319
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Oligonucleotides by LC–MS/MS: The Challenges of Quantifying A Phosphorothioate Oligonucleotide and Multiple Metabolites

Abstract: We show that quantification of an oligonucleotide and multiple metabolites, including isobaric 3´ and 5´ metabolites, is achievable in a single assay through good sample clean-up and careful optimization of the LC-MS/MS parameters. The strategy presented here can be applied elsewhere and may be useful for other oligonucleotides and their metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…It has been reported that the detection sensitivity of nucleic acids changes when additives, such as citrate, are added to the matrix solution . Moreover, amines such as TEA are commonly added when oligonucleotides are analyzed by LC/MS . Therefore, in this study, we selected optimized amine additives such as MA, DMA or TEA to improve the detection sensitivity of LNA‐A.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the detection sensitivity of nucleic acids changes when additives, such as citrate, are added to the matrix solution . Moreover, amines such as TEA are commonly added when oligonucleotides are analyzed by LC/MS . Therefore, in this study, we selected optimized amine additives such as MA, DMA or TEA to improve the detection sensitivity of LNA‐A.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, a similar extraction approach as described by the authors of the 18-mer Trabedersen assay was assessed [33]. This method combined an LLE method using chloroform-phenol-isoamylalcohol with a hydrophilic-lipophilicbalanced SPE.…”
Section: Mixed-mode Anion Exchange Spe Methods Developmentmentioning
confidence: 99%
“…Various approaches for ODN extraction from the biological matrix have been used including protein precipitation, liquid-liquid extraction (LLE) and SPE, though each method has its own shortcomings and compound-dependent success rates [27,[29][30][31][32][33].…”
mentioning
confidence: 99%
“…A similar issue has been encountered by Zhang et al, 80 who determined PS ASOs in rat plasma at relatively low LLOQ value (5 ng mL À1 ), but without complete separation. Such a problem has been largely solved by Ewles et al 81 by the application of accurate sample clean up, careful optimization of MS parameters, and selection of chromatographic parameters. The separation of 20 mer PS and 3 0 N-1-3 0 N-3 as well as 5 0 N-1-5 0 N-3, and their quantication with LLOQ values in the range of 2-1000 ng mL À1 were obtained.…”
Section: Golodirsen (Vyondys 53™)mentioning
confidence: 99%